Evolución temporal de las hospitalizaciones por tuberculosis extrapulmonar en la población chilena entre los años 2002-2022 = Temporal evolution of hospitalisations due to extrapulmonary tuberculosis in the Chilean population between 2002 and 2022 - Burgos Escobar, Ignacio; Leiva-Escobar, Ignacio; Lamadrid, Angelo (Revista chilena de infectología)
Background: Tuberculosis (TB) is a serious global public health problem owing to its high morbidity and mortality rates. While primarily affecting the lungs, it can spread to other parts of the body, resulting in extrapulmonary TB. Aim: To describe and characterize the temporal evolution of hospitalizations for extrapulmonary TB in the Chilean population from 2002 to 2022. Materials and Methods: A review of the country’s hospital discharges for extrapulmonary TB was conducted for 2002-2022. The sociodemographic characteristics of the population were described, the prevalence of hospitalizations for extrapulmonary TB was estimated, and the temporal pattern was assessed using joinpoint regression.  Results: During the study period, 5,513 hospital discharges were recorded.  The average prevalence was 1.5 cases per 100,000 inhabitants. Hospitalizations exhibited a downward trend from 2002 to 2012, followed by a slight, albeit non-statistically significant, increase from 2012 to 2022. Conclusion: In Chile, 1.5 per 100,000 people required hospitalization for extrapulmonary TB between 2002 and 2022. To reduce the spread and progression of the extrapulmonary form of TB, we suggest strengthening public policies that promote prevention and prompt treatment.